Brave : the story of Ahinoam [large type] - Andrews, Mesu, 1963- (King David's brides, 2024)
"In the tumultuous world of ancient Israel, Ahinoam -- a dagger-wielding Kenite woman -- flees her family farm with her unconventional father to join the ragtag band of misfits led by the shepherd-turned-warrior David ben Jesse. As King Saul's treasonous accusations echo through the land, Ahinoam's conviction that David's anointing makes him Yahweh's chosen king propels her on a perilous journey to Moab and back into Judah's unforgiving wilderness, only to encounter more hardship and betrayal. Amid the challenges, Ahinoam forges an unexpected bond with David's sister and gains respect among David's army through her knowledge of Kenite metalworking. Though some offer friendship, Ahinoam, scarred by past relationships, isolates to avoid more pain and refuses to acknowledge her growing feelings for the renegade king. As Ahinoam's heart grapples for footing, King Saul's army closes in, and Ahinoam must confront the true meaning of love, loyalty, and courage. Is she brave enough to trust new friends and love Israel's next king?"--